2023
DOI: 10.1371/journal.pone.0281122
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of PID controller and fuzzy logic controller for DC-DC boost converter

Amil Daraz,
Abdul Basit,
Guoqiang Zhang

Abstract: Demand of Power electronics converter is increased due to the rapid increase of green re-sources. The distributed nature of uncontrolled renewable energy resources are connected with the grid via power electronics converter. DC-DC converters are high-frequency current conversion circuits that use transformers, inductors, and capacitors to smooth switching noise into regulated DC voltages. In this study, a comparative performance analysis of Proportional integral Derivative (PID) and fuzzy logic controller (FLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They employed an optimal control approach [ 8 ] to minimize the tracking error of the ball. The results demonstrated that Fuzzy PID [ 9 11 ] exhibits superior performance and algorithmic efficiency compared to traditional PID. A more complex problem is addressed by utilizing the sliding mode controller [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They employed an optimal control approach [ 8 ] to minimize the tracking error of the ball. The results demonstrated that Fuzzy PID [ 9 11 ] exhibits superior performance and algorithmic efficiency compared to traditional PID. A more complex problem is addressed by utilizing the sliding mode controller [ 12 ].…”
Section: Introductionmentioning
confidence: 99%